Yield formation at different nodes in the ratoon season of “forage–grain ratoon rice” under cutting time and stubble height - Gai, Panpan; Chen, Yuanwei; Sun, Xin; Chen, Hongjing; Yang, Desheng; Ren, Miaofei; Liu, Lei; Wang, Weiqin; Zheng, Huabin; Tang, Qiyuan (Frontiers in Plant Science, 2025)
IntroductionBased on “forage–grain ratoon rice,” the planting pattern of a high-grain-yield ratoon crop (RC), supplemented by fodder, can be regulated by the cutting time and stubble height.MethodsIn 2021 and 2022, using Xiangliangyou 900 as the experimental material, field trials were conducted to investigate differences in the yield formation of regenerated tillers from different nodal positions under varying cutting times (i.e., 10 and 30 days after heading, T10 and T30, respectively) and stubble heights (i.e., 10 and 30 cm, H10 and H30, respectively).ResultsThe results showed that the average grain yield of T10 was 80.48% higher than that of T30, while the average grain yield of H30 was 21.77% higher than that of H10. Analysis revealed that the higher yield of T10 could be attributed to the panicle per square meter and the grain filling, while the higher yield of H30 could be attributed to the panicle per square meter. Analysis also revealed that the panicle per square meter and the grain filling of regenerated tillers at different nodes in T10 were higher than those in T30, while the yield performance of regenerated tillers at different nodes in H was more complex. Further analysis revealed that, under the H30 treatment, the grain yield generally followed the order D4 > D3 > D2, with D3 and D4 contributing approximately 84.80% of the total yield on average. In contrast, under the H10 treatment, D3 exhibited a higher yield than D4, with D3 contributing approximately 58.05% of the total yield. Notably, the D3 yield under H10 was higher than that under H30, while D4 showed the opposite trend.DiscussionReasonable cutting times and stubble heights are important factors to increase the yield of the ratoon season.